A Monastery for Laypeople: Birken Forest Monastery and the Monasticization of Convert Theravada in Cascadia - Ferguson, Karen (Journal of global buddhism, 2022)
Theravada as practiced by most converts in the West is distinguished by the absence of monasticism, its dominant institution. Nevertheless, Thai Forest monasticism has managed to gain a foothold in the convert West, thanks to the efforts of convert monastics trained in Thailand. This article analyzes the missionary project to "monasticize" Western lay converts through the history of Birken Forest Monastery in British Columbia, Canada, founded in 1994. To establish a monastery in Birken’s isolated, non-Buddhist environs, the abbot, Ajahn Sona in effect created a lay village to attract converts to and to teach them their role in orthodox Thai Forest monasticism. The all-consuming nature of the monasticization project among laypeople has cut short the training of a homegrown Sangha at Birken, demonstrating the challenges of establishing a domestic convert monasticism and the continuing dominance of the laity in North American Theravada.